Premalignant quiescent melanocytic nevi do not express the MHC class I chain-related protein A - Fuertes, Mercedes Beatriz (2011)
The MHC class I chain-related protein A (MICA) is an inducible molecule almost not expressed by normal cells but strongly up-regulated in tumor cells. MICA-expressing cells are recognized by natural killer (NK) cells, CD8+ abTCR and gdTCR T lymphocytes through the NKG2D receptor. Engagement of NKG2D by MICA triggers IFN-g secretion and cytotoxicity against malignant cells. Although most solid tumors express MICA and this molecule is a target during immune surveillance against tumors, it has been observed that high grade tumors from different histotypes express low amounts of cell surface MICA due to a metalloprotease-induced shedding. Also, melanomas develop after a complex process of neotransformation of normal melanocytes. However, the expression of MICA in premalignant stages (primary human quiescent melanocytic nevi) remains unknown. Here, we assessed expression of MICA by flow cytometry using cell suspensions from 15 primary nevi isolated from 11 patients. When collected material was abundant, cell lysates were prepared and MICA expression was also analyzed by Western blot. We observed that MICA was undetectable in the 15 primary nevi (intradermic, junction, mixed, lentigo and congenital samples) as well as in normal skin, benign lesions (seborrheic keratosis), premalignant lesions (actinic keratosis) and benign basocellular cancer. Conversely, a primary recently diagnosed melanoma showed intense cell surface MICA. We conclude that the onset of MICA expression is a tightly regulated process that occurs after melanocytes trespass the stage of malignant transformation. Thus, analysis of MICA expression in tissue sections of skin samples may constitute a useful marker to differentiate between benign and malignant nevi.